Onlay versus Inlay humeral steam in Reverse Shoulder Arthroplasty (RSA): clinical and biomechanical study - Beltrame, Alessandro; Di Benedetto, Paolo; Cicuto, Chiara; Cainero, Vanni; Chisoni, Renato; Causero, Araldo (Acta Biomedica Atenei Parmensis, 2019)
Background and aim of the work: Reverse shoulder arthroplasty (RSA) is becoming treatment of choice in glenohumeral arthropathies with massive lesion of the rotator cuff, due to a gradual extension of indications and new designs that provide better outcome. In this study we compared two different reverse shoulder prosthesis designs, defined as Inlay (or typical Grammont type) and a relatively new model defined as Onlay (that preserves tuberosity bone stock). We analyzed clinical, biomechanical and radiological outcomes, as well as complications of RSA in these two groups. Methods: We performed a prospective study on a population of 42 patients undergoing Reverse Shoulder Replacement by a single expert surgeon. We consider 21 patients (group A) who underwent to reverse shoulder replacement with a curved onlay steam with 145° inclination (Ascend Flex group, Wright medical, Memphis, TN, USA) and 21 patients who underwent to reverse shoulder replacement with a traditional Inlay Grammont steam (Modular Shoulder System SMR, Systema Multiplana Randelli; Lima-LTO, San Daniele del Friuli, Italy) between August 2010 and October 2018. We studied the following items: active range of motion (AROM), radiological parameters (lateralization shoulder angle LSA, Distalization Shoulder Angle DSA), functional scale (Constant-Murley Score), post-operative complications (infection, aseptical implant mobilitazion, residual pain, scapular notching, fractures, tuberosity reabsorbtion, dislocation, bleedings, nerve palsy, pulmonary embolus). Results: A significant improvement in ROM and functional score (Constant Shoulder Score) were observed in both groups. Group A (Onlay design 145°, medial tray) provides improvement in adduction, extension and external rotation compared to group B. No significant differences were found in abduction, external rotation and forward flexion. At 6 months follow-up, pain relief was detected in all patients. Although complications occur in a high percentage of patients in literature, no postoperative complications were observed in our cases series. Conclusions: Our results showed how RSA is a real solution to improve quality of life and to restore pain-free shoulder ROM in patients where cuff tear arthropathy occurs. Onlay design 145° may provides better active external rotation, extension, adduction: it is necessary to continue follow up and include more cases to prove these data.